Impact of physical vanity, achievement vanity and brand equity on the consumption of luxury skincare products - Wani, Showkat Khalil (Business: Theory and Practice, 2025)
The aim of this study is to evaluate the influence of physical Vanity, achievement vanity, and brand equity on luxury consumption in the skincare industry, considering the promising US$13.9 billion beauty and personal care market in India, as estimated by Euromonitor International. Data were collected from 200 male and female participants in the National Capital Region of Delhi, India, belonging to various geographic groups and income levels. Confirmatory factor analysis was utilized to assess the relationship between observed and latent variables, while regression analysis was employed to determine the impact of physical Vanity, achievement vanity, and brand equity on luxury consumption. The study reveals that physical Vanity, achievement vanity, and brand equity positively affect luxury product consumption, with brand equity having the most significant impact. The associations between luxury consumption and physical Vanity, achievement vanity, and brand equity were found to be statistically meaningful. The findings offer valuable insights for skincare market marketers, allowing them to identify opportunities and strategize to capture untapped markets in the country. Additionally, the results enable them to understand the relative influence of the three factors – physical Vanity, achievement vanity, and brand equity – on luxury consumption. This research contributes to the understanding of the positive effects of physical Vanity, achievement vanity, and brand equity on luxury product consumption. The survey-based approach offers a comprehensive yet succinct overview of the existing literature and its implications, benefiting both luxury brand managers and future researchers.